International comparison of vocational pre-service teachers' character education in Indonesia and Malaysia - Jaedun, Amat; Raharjo, Nuryadin; Hastutiningsih, Arum Dwi; Sutarto, Sutarto; Pratama, Galeh Nur Indriatno Putra; Masek, Alias bin (Jurnal Cakrawala Pendidikan, 2024)
This study examines the commitment of vocational teacher education students at Universitas Negeri Yogyakarta, Indonesia, and Universiti Tun Hussein Onn Malaysia (UTHM) in applying core character values. The global trend in teacher education links education and economic growth, emphasizing students' competence for the job market. However, teachers are also expected to address social and moral cohesion in the younger generation. The research involved 177 third- and fourth-year students at FPTV UTHM Malaysia and an equal number at FT-UNY, utilizing a questionnaire based on core character values. The findings indicate moderate commitment levels (58.75%) among university students. UTHM students scored slightly higher (2.42) than UNY students (2.28). The study shows that character education for vocational teacher education students in both Indonesia and Malaysia has not reached optimal levels, emphasizing the need to investigate more effective character education models for future vocational teachers.